Potential and Economic Viability of Freshwater Prawn Macrobrachium rosenbergii (de Man, 1879) Polyculture with Indian Major Carps in Northwestern Bangladesh - Jasmine, S.; Molina, M.; Hossain, M.Y.; Jewel, M.A.S.; Ahamed, F.; Fulanda, B. (Our Nature, 2012)
This study was conducted to assess the aquaculture potential of the freshwater prawn Macrobrachium rosenbergii (de Man, 1879) with the Indian major carps (Catla, Catla catla; Rui, Labeo rohita and Mrigal, Cirrhinus mrigala) and silver carp, Hypophthalmichthys molitrix in northwestern Bangladesh. Further, the effect of the culture system on overall production and economic feasibility was evaluated. A 3×2 (treatment×replicate) experimental setup was conducted using six earthen ponds measuring 100 m2 each for a culture period of six months from September, 2007 to February, 2008. The treatments were as follows: T1 was stocked with only carps (catla, rohu, mrigal and silver) at the 3000 (catla), 2000 (ruhu), 3000 (mrigal) and 2000 (silver) ha-1; T2 and T3 were stocked with catla and silver carp were 3000 and 2000 ha-1, respectively; and additionally M. rosenbergii (juvenile) was stocked at 15000 and 20000 ha-1 in T2 and T3, respectively. All the ponds were subjected to the same fertilization treatment. Fish were fed twice per day at a rate of 5-12% of the prawn and fish body weight. The net weight gain of catla and silver carp were 69.08±11.63 and 108.67±15.00 g in T1, 61.76±12.58 and 98.80±17.05 g in T2, while 58.11±12.51 and 93.09±14.84 g in T3, respectively. The mean individual weight of harvested prawn was significantly higher in T2 (14.61±02.06 g) than T3 (14.04±01.83 g) (P<0.05). Also the survival rate of prawn was higher in T2 (74.15%) than T3 (69.25%) (P<0.05). The net production of prawn was higher in T3 (1141.28±46.35 kg ha-1) than T2 (964.54±25.53 kg ha-1), but the specific growth rate was significantly higher in T2 (2.07%) than T3 (1.99%) (P<0.05). Higher profit was obtained in T3 (35682.18 Tk ha-1) than T1 (8537.53 Tk ha-1) and T2 (30801.56 Tk ha-1); however, cost-benefit ratio (CBR) was significantly higher in T2 (3.19) where stocking densities of prawn was 15000 ha-1 than T1 (2.92) and T3 (2.47). The results of this experiment indicate that the polyculture of the freshwater prawn with the Indian major and Chinese carp present a more profitable venture which is more economically feasible than the monoculture of the freshwater prawn. DOI: http://dx.doi.org/10.3126/on.v9i1.5735